2023
DOI: 10.3390/healthcare11111555
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Using a Shoulder/Scapular Brace on the Posture and Muscle Activity of Healthy University Students during Prolonged Typing—A Randomized Controlled Cross-Over Trial

Abstract: Laptop use appears to contribute to poor working postures and neck pain among university students. Postural braces have the potential to improve upper back/neck posture and therefore might have a role as an ergonomic aid for this population. Therefore, the purpose of this study was to assess the short-term effects of scapular bracing on pain, fatigue, cervicothoracic posture, and the activity of the neck and upper-back muscles in healthy college students. A randomized controlled crossover trial was conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Velcro is one of the best-known and commercially successful biomimetic materials which is used in various fields such as the biomedical, textiles, footwear, prosthesis fields, and so on. Thus, Velcro straps have been employed in postural braces used to restore normal scapular posture and scapular muscle activation (Figure 3) [26]. Velcro is also used for attaching wearable systems such as e-sleeves with an open and Velcro closure structure (Figure 4) for stroke rehabilitation by functional electrical stimulation (FES) [26].…”
Section: Plants As Inspiration In Developing Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Velcro is one of the best-known and commercially successful biomimetic materials which is used in various fields such as the biomedical, textiles, footwear, prosthesis fields, and so on. Thus, Velcro straps have been employed in postural braces used to restore normal scapular posture and scapular muscle activation (Figure 3) [26]. Velcro is also used for attaching wearable systems such as e-sleeves with an open and Velcro closure structure (Figure 4) for stroke rehabilitation by functional electrical stimulation (FES) [26].…”
Section: Plants As Inspiration In Developing Materialsmentioning
confidence: 99%
“…Thus, Velcro straps have been employed in postural braces used to restore normal scapular posture and scapular muscle activation (Figure 3) [26]. Velcro is also used for attaching wearable systems such as e-sleeves with an open and Velcro closure structure (Figure 4) for stroke rehabilitation by functional electrical stimulation (FES) [26]. Another remarkable example is the lotus flower, renowned for its incredible self-cleaning properties.…”
Section: Plants As Inspiration In Developing Materialsmentioning
confidence: 99%
“…Regarding the first type, the figure-eight orthopedic device, research conducted by Lee and his team [12] found that combining scapular posterior tilting exercises with this type of shoulder brace yielded significantly more favorable results in reducing RSP among young adult males compared to exercises without bracing [12]. More recently, Leung et al [19] found that the use of a commercially available scapular brace seems to result in an immediate decrease in electromyography activity in the LT muscles in healthy university students while they engage in prolonged typing. Additionally, Chiu and his team showed that the characteristics of shoulder brace straps influence muscle activity and scapular motion at various arm angles, with diagonal braces with maximum strap tension being effective in alleviating RSP and impingement syndrome [20].…”
Section: Introductionmentioning
confidence: 99%